2023
DOI: 10.1002/ese3.1449
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of rock stratum structure on the stability of weakly cemented layered floor and the floor control measures: A case study of Meihuajing Mine

Abstract: Given the deformation and instability of the layered floor of weakly cemented soft rock roadway, taking the mining roadway of Meihuajing Mine as the engineering background, the deformation and instability mechanism of the floor and the control measures of the surrounding rock under different stratum combination conditions are studied by using the methods of field investigation, numerical calculation and field test. The results show that: (1) the layered characteristics of surrounding rock in weakly cemented so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The extensive engineering practices have demonstrated that the layered structure of rocks is one of the significant factors contributing to floor heave [23][24][25][26]. Common layered rocks include schist, gneiss, slate, and shale.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive engineering practices have demonstrated that the layered structure of rocks is one of the significant factors contributing to floor heave [23][24][25][26]. Common layered rocks include schist, gneiss, slate, and shale.…”
Section: Introductionmentioning
confidence: 99%